Beyond the limit - Dees, Cindy (Dees, Cindy. Valkyrie Ops., 2019)
"Team Reaper has a new mission... Train the first female SEALs. Navy SEAL Griffin Caldwell is not happy with his team's top-secret mission, training the first female SEALs. Griffin's determined to prove that that his trainee Sherri Tate - a former beauty queen no less - doesn't have what it takes to join the world's most elite warrior's club. Until he sees what she's capable of, and even this hard-nosed SEAL has to admit she's tough as nails. What he won't admit to is the attraction sizzling between them. Navy media officer Sherri Tate is more than just a pretty face. When she's given the opportunity to achieve her dream of becoming a SEAL, she won't let anything stand in her way, not even her arrogant trainer, who is too sexy for words. When a dangerous mission lands Sherri and Griffin in the cross hairs of the world's most feared terrorist, it's going to take everything they have to come out with their lives - and hearts - intact."--Publisher description.